RELEVANSI PEMIKIRAN FILSAFAT ISLAM PERSPEKTIF MUHAMMAD IQBAL TERHADAP PENDIDIKAN ISLAM DI ERA MODERN - Febi Febrianda; Nunu Burhanuddin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study examines the relevance of Muhammad Iqbal's Islamic philosophical thought to Islamic education in the modern era. Iqbal, as one of the greatest thinkers of the Islamic world, made a significant contribution to the understanding of the relationship between religion, education, and intellectual progress. In his view, education is not only aimed at creating technically skilled individuals, but also to shape character and deepen spirituality. Iqbal's thought emphasizes the importance of integration between science, faith, and the formation of self-awareness (selfhood) in the Islamic context. This paper will identify several key concepts in Iqbal's educational philosophy, such as the concept of "Khudi" (self-awareness), the development of human potential, and thoughts on the role of religion in intellectual progress. This type of research is a qualitative literature research that examines theory in depth to get conclusions. The results of this study show that the relevance of these ideas is analyzed in the context of Islamic education today, which is faced with the challenges of globalization, technological advancement, and cultural pluralism. It is hoped that the results of this analysis can provide new insights for the development of more relevant and holistic Islamic education in the modern era, which is able to bridge the gap between traditional Islamic values and the needs of contemporary society